Does UK medical education provide doctors with sufficient skills and knowledge to manage patients with eating disorders safely?. Issue 1113 (4th June 2018) - Ayton, Agnes; Ibrahim, Ali
Abstract: Background: Eating disorders affect 1%–4% of the population and they are associated with an increased rate of mortality and multimorbidity. Following the avoidable deaths of three people the parliamentary ombudsman called for a review of training for all junior doctors to improve patient safety. Objective: To review the teaching and assessment relating to eating disorders at all levels of medical training in the UK. Method: We surveyed all the UK medical schools about their curricula, teaching and examinations related to eating disorders in 2017. Furthermore, we reviewed curricula and requirements for annual progression (Annual Review of Competence Progression (ARCP)) for all relevant postgraduate training programmes, including foundation training, general practice and 33 specialties. Main outcome measures: Inclusion of eating disorders in curricula, time dedicated to teaching, assessment methods and ARCP requirements. Results: The medical school response rate was 93%. The total number of hours spent on eating disorder teaching in medical schools is <2 hours. Postgraduate training adds little more, with the exception of child and adolescent psychiatry. The majority of doctors are never assessed on their knowledge of eating disorders during their entire training, and only a few medical students and trainees have the opportunity to choose a specialist placement to develop their clinical skills. Conclusions: Eating disorder teaching is minimal during the 10–16 years of undergraduate and postgraduate medical training in the UK. Given the risk of mortality and multimorbidity associated with these disorders, this needs to be urgently reviewed to improve patient safety.